Laparoscopic Sentinel Node Navigation Surgery for Stomach Preservation in Patients With Early Gastric Cancer: A Randomized Clinical Trial. Issue 21 (20th July 2022) - Kim, Young-Woo; Min, Jae-Seok; Yoon, Hong Man; An, Ji Yeong; Eom, Bang Wool; Hur, Hoon; Lee, Young Joon; Cho, Gyu Seok; Park, Young-Kyu; Jung, Mi Ran; Park, Ji-Ho; Hyung, Woo Jin; et al.
Abstract : PURPOSE: To compare postoperative complications, long-term survival, and quality of life (QOL) after laparoscopic sentinel node navigation surgery (LSNNS) and laparoscopic standard gastrectomy (LSG). METHODS: Five hundred eighty patients with preoperatively diagnosed stage IA gastric adenocarcinoma (≤ 3 cm) were assigned to undergo either LSG or LSNNS. Observers were not blinded to patient grouping. The primary outcome was 3-year disease-free survival (3y-DFS). Secondary outcomes included postoperative complications, QOL, 3-year disease-specific survival (3y-DSS), and 3-year overall survival (3y-OS). RESULTS: In total, 527 patients were included in the modified intention-to-treat analysis population for the primary outcome (LSG, 269; LSNNS, 258). Stomach-preserving surgery was performed in 210 patients (81%) in the LSNNS group. During the median follow-up duration, the 3y-DFS rates in the LSG and LSNNS groups were 95.5% and 91.8%, respectively (difference: 3.7%; 95% CI, –0.6 to 8.1). Three patients with recurrence and five with metachronous gastric cancer in the LSNNS group underwent standard surgery. Two patients with distant metastasis in both groups were treated with palliative chemotherapy. The 3y-DSS and 3y-OS rates in the LSG and LSNNS groups were 99.5% and 99.1% ( P = .59) and 99.2% and 97.6% ( P = .17), respectively. Postoperative complications occurred in 19.0% of the LSG group and 15.5% of the LSNNS group ( P = .294). The LSNNS group showed better physical function ( P = .015), less symptoms ( P < .001), and improved nutrition than the LSG group. CONCLUSION: LSNNS did not show noninferiority to LSG for 3y-DFS, with a 5% margin. However, the 3y-DSS and 3y-OS were not different after rescue surgery in cases of recurrence/metachronous gastric cancer, and LSNNS had better long-term QOL and nutrition than LSG.